The Characteristic Of Caretaker Speech Of Native Speaker Of English: Conversation Found In Imagine That Movie - Pambudi, Dewi Sri, Prof. Dr. Endang Fauziati, M.Hum, Dr. Dwi Haryanti, M.Hum (2015)
This research aims at describing the types of language form found in Imagine That movieand the types of language function found in Imagine That movie. The type of this research is descriptive qualitative research.Theobjects of the research are only focuses on speech adults of caretaker on native speaker. Subject of this research are the caretakers found in Imagine That movie such as father, mother, etc. The data to be analyzed in this research paper are utterances produce by caretaker speech on native speaker. The data source is the movie entitled Imagine That and its manuscript.The writer used the manuscript of conversation Imagine Thatfilm of the caretaker speech method of collect data.The steps are: the writer watched the original film and read the movie script of Imagine That movie. After that the writer underlined the caretaker utterances then wrote down into the paper. The result of this research show there four characteristic of caretaker speech: tone of voice, addressing what children are doing, many ways of saying different things, simple utterance and the use of name. Then, there are seven kinds of language function: instrumental function, interactional function, regulatory function, imaginative function, personal function, representational function, and heuristic function.